2022
DOI: 10.2147/ijgm.s366348
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Risk Factors and Macular Thickness in Patients with Early Diabetic Retinopathy

Abstract: The purpose of this study was to explore the changes in macular thickness (MT) in normal people, patients without obvious diabetic retinopathy (NDR) and patients with nonproliferative diabetic retinopathy (NPDR) and to study the possible risk factors for early diabetic retinopathy (DR). Methods: Thirty-one healthy individuals, 40 people with no sign of DR and 60 people with mild NPDR were included in this crosssectional study. All patients underwent a complete ophthalmological examination. Optical coherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…Our study also provided data on the macular thickness measurements in patients with diabetes with and without DR, which showed that the macular thickness was lower in patients without DR when compared with the DR group. These results were similar to recent study by Wei et al [14] which found that MT in the NDR group was much lower than that in the NPDR group, demonstrating that OCT can detect MT that gradually deteriorates with the development of DR. Similar to our findings, Murugesan et al [27] found that MT in patients with T2DM without DR was thinner than the general population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study also provided data on the macular thickness measurements in patients with diabetes with and without DR, which showed that the macular thickness was lower in patients without DR when compared with the DR group. These results were similar to recent study by Wei et al [14] which found that MT in the NDR group was much lower than that in the NPDR group, demonstrating that OCT can detect MT that gradually deteriorates with the development of DR. Similar to our findings, Murugesan et al [27] found that MT in patients with T2DM without DR was thinner than the general population.…”
Section: Discussionsupporting
confidence: 92%
“…Huang et al [13] found that CT decline was in fact strongly related to DR after controlling these factors. These factors might also be risk factors or even predictors of diabetic macular edema (DME), as well as contributing to changes in macular thickness (MT) in patients with diabetes [14]. The early diagnosis of the emergence of DR and a subsequent management may result from measuring MT in patients [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the inner retinal ring may be more susceptible to the severity of obesity. A study by Wei et al [29] found a significant difference in the macular thickness within the inner 3 mm ring, but not the 6 mm outer ring, in diabetic patients without retinopathy compared to healthy controls. This result aligns with our findings and may suggest that the inner retina may be more susceptible to metabolic changes.…”
Section: Discussionmentioning
confidence: 93%
“…[36] This study also found that SBP and FPG were risk factors for DR, which is consistent with the results of previous studies. [37,38]…”
Section: Discussionmentioning
confidence: 99%